2014
DOI: 10.1111/scs.12136
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare professionals' knowledge, attitudes and skills regarding patient safety: a systematic literature review

Abstract: The purpose of this literature review was to determine the extent of existing knowledge about healthcare professionals' knowledge, attitudes and skills related to patient safety. A systematic review was performed using two electronic databases: MEDLINE (Ovid) and CINAHL (EBSCO) for the period 2000-2012. The inclusion criteria were peer-reviewed articles or empirical studies, published in English. The focus groups of the study were physicians, head nurses, nurses and nurse assistants. Altogether, 18 studies met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 45 publications
(79 reference statements)
3
27
0
Order By: Relevance
“…The participants reported that when a skilled surgeon and competent surgical team performed RALS, the potential for reduced operative time and better patient outcomes were increased. These findings are consistent with previous research (Brasaite, Kaunonen, & Suominen, 2015;Gershman et al, 2016;Sexton et al, 2018).…”
Section: Discussionsupporting
confidence: 94%
“…The participants reported that when a skilled surgeon and competent surgical team performed RALS, the potential for reduced operative time and better patient outcomes were increased. These findings are consistent with previous research (Brasaite, Kaunonen, & Suominen, 2015;Gershman et al, 2016;Sexton et al, 2018).…”
Section: Discussionsupporting
confidence: 94%
“…Higher positive attitude than gained knowledge toward patient safety pinpointed in this study is a common finding throughout related studies [12,15,17,19]. Strikingly, there was not any correlation between knowledge and attitudes of participants in the current study.…”
Section: Discussionsupporting
confidence: 60%
“…The median years since fellowship completion was 13 years in a study by Berman et al [15], which was an online survey, conducted on 353 surgeons addressing knowledge, attitudes, and perceptions surrounding the culture of patient safety. In a systematic review conducted by Brasaite et al, most of the health care professionals had many years of work experience (mean = 23.9 years) and their mean age was 46.7 years [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although demands for effectiveness are high in surgical wards, quality of care and patient safety must also be secured. However, a recent systematic review reports that healthcare systems face a major challenge in ensuring safe care and preventing harm. Although many healthcare professionals have a positive attitude towards patient safety, their knowledge of safety issues continues to be reported as deficient.…”
Section: Introductionmentioning
confidence: 99%